1970
DOI: 10.1063/1.3022064
|View full text |Cite
|
Sign up to set email alerts
|

The stability of the bicycle

Abstract: Almost everyone can ride a bicycle, yet apparently no one knows how they do it. I believe that the apparent simplicity and ease of the trick conceals much unrecognized subtlety, and I have spent some time and effort trying to discover the reasons for the bicycle's stability. Published theory on the topic is sketchy and presented mainly without experimental verification. In my investigations I hoped to identify the stabilizing features of normal bicycles by constructing abnormal ones lacking selected features (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 1 publication
1
95
0
2
Order By: Relevance
“…It can nevertheless be shown that these weak effects contribute their share to the stability of the system. [68] Jones [13] experimentally determined that gyroscopic action plays a relatively minor role in the riding of a bicycle at normal speeds. Jones wanted to design an unridable bicycle, and he investigated the effects of gyroscopic action experimentally by mounting a second wheel on the front fork to cancel or augment the angular momentum of the front wheel.…”
Section: Gyroscopic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can nevertheless be shown that these weak effects contribute their share to the stability of the system. [68] Jones [13] experimentally determined that gyroscopic action plays a relatively minor role in the riding of a bicycle at normal speeds. Jones wanted to design an unridable bicycle, and he investigated the effects of gyroscopic action experimentally by mounting a second wheel on the front fork to cancel or augment the angular momentum of the front wheel.…”
Section: Gyroscopic Effectsmentioning
confidence: 99%
“…Its "feel" was a bit strange, a fact I attribute to the increased moment of inertia about the front forks, but it did not tax my (average) riding skill even at low speed. [13] Klein and students at the University of Illinois at Urbana-Champaign (UIUC) conducted a number of precession canceling and altering experiments in the 1980s based on two experimental bicycles that are similar except for the front fork geometries. The bicycle in Figure 11 has an unaltered steering head and a positive trail.…”
Section: Gyroscopic Effectsmentioning
confidence: 99%
“…The closest model to our purposes is [7] which considers a bicycle as a nonlinear, nonholonomic, non-minimum phase system. The stability and control of a bicycle are also of interest [11], [8], as well as the study of its aerodynamics [5].…”
Section: The Vehicle Control and Degrees Of Freedommentioning
confidence: 99%
“…It seems clear that the gyroscopic contribution is not the main assistance to guarantee the stability of a bicycle, but however the problem is not completely solved yet [Jones, 1970;Cleary et al, 2011;Kooijman et al, 2011].…”
Section: Introductionmentioning
confidence: 99%